Effectiveness of Natural Fiber/Agricultural Waste Materials as Thermal Insulation - Raudhah Nur Evana Edwin; Ariesya Farhana Zulkefli; Hasya Mastura Mohaidi; Hawa Helena Azi Riza; Nurul Syazwani Mohd Suffian; Nur Damia Batrisyia Irwan Syah; Muhammad Afwan Ismail; Nur Farrah Syazwalina Azizuddin (Malaysia Journal of Invention and Innovation, 2024)
Sugarcane fiber, coconut fiber and palm oil fiber are the examples of renewable and eco- friendly materials that is usually being implemented as thermal insulation which provides promising alternative compared to artificial options. Previous studies have proven the efficacy of these agricultural by-product in heat insulation for building construction, mechanical system and so on. In those studies, the specimen is in a form of compressed or added with binding agent for further characterization regarding its thermal properties. This study emphasizes on investigation regarding the viability of using coconut peat, sugarcane dregs and palm oil fiber in its dried and uncompressed form as thermal insulation. A temperature difference measurement was conducted to determine the capability of each of the material to retain heat as the result of the material attachment on a surface, without the addition of binding agent. From this study, it was found that each of this material has the capability to retain heat when used as surface insulating element. The sugarcane dregs (dried and uncompressed form) is proven to be most effective in retaining heat, followed closely by palm oil fiber in comparison with the uninsulated control set of experiment.